2014
DOI: 10.1038/mp.2014.119
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and cortisol reactivity in children of depressed mothers

Abstract: A growing body of research demonstrates that individuals diagnosed with major depressive disorder (MDD) are characterized by shortened telomere length, which has been posited to underlie the association between depression and increased instances of medical illness. The temporal nature of the relation between MDD and shortened telomere length, however, is not clear. Importantly, both MDD and telomere length have been associated independently with high levels of stress, implicating dysregulation of the hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
112
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(122 citation statements)
references
References 59 publications
5
112
1
Order By: Relevance
“…When the sample in this study is stratified by sex, the association between delay discounting and LTL is observed in females but not in males. Our findings are in agreement with earlier evidence that females are more sensitive to social adversity and stress (28,29,63) with respect to cellular aging. Overall, shortened LTL mirrors the cell's mitotic history and replicative history of hematopoietic stem cells, and is further subjected to the effects of inflammation and oxidation (36,37,64).…”
Section: Discussionsupporting
confidence: 93%
“…When the sample in this study is stratified by sex, the association between delay discounting and LTL is observed in females but not in males. Our findings are in agreement with earlier evidence that females are more sensitive to social adversity and stress (28,29,63) with respect to cellular aging. Overall, shortened LTL mirrors the cell's mitotic history and replicative history of hematopoietic stem cells, and is further subjected to the effects of inflammation and oxidation (36,37,64).…”
Section: Discussionsupporting
confidence: 93%
“…Four saliva samples were collected throughout these tasks to obtain cortisol levels. Among other findings, the results have shown that shorter telomeres were associated with higher cortisol reactivity, not to basal level of cortisol, suggested a vulnerability to develop illnesses later, such as major depressive disorder (Gotlib et al, 2015).…”
Section: Telomeresmentioning
confidence: 77%
“…According to a study conducted by Gotlib et al (2015), a shortened telomere is a risk factor for developing major depressive disorder. The researchers recruited ninety-seven 10-to 14-year-old girls, who had not experienced psychological disorders, to participate in the study.…”
Section: Telomeresmentioning
confidence: 99%
“…For instance, Gotlib et al showed that children at familial risk of developing major depressive disorder (MDD) had shorter LTL compared to controls, even before manifesting an onset of depression. 3 Michalek et al analyzed genetic polymorphisms of telomerase components (TERT and TERC) as predictors of LTL to demonstrate that shortened telomeres might increase risk for early-onset recurrent MDD in a large sample of cases and controls. 4 In this context, shortened TL was considered as a susceptibility marker for MDD that is present before illness onset.…”
mentioning
confidence: 99%